Project Management of risks and environmental changes in the Middle Ebro: river restoration and territorial resilience.: Research note - Ollero Ojeda, Alfredo (Geographicalia, 2023)
This research note characterises the project Management of risks and environmental changes in the middle Ebro: river restoration and territorial resilience. It is the coordinating project of the SEDEXCHARE macroproject (Sediment, hydrological extremes, historical-environmental changes and fluvial resilience: the river Ebro). As a whole, the aim is to build an Observatory of the Ebro River: of its fluvial functioning, its natural and human evolution, its environmental problems and its risks.
Keywords: risk management; environmental change; river restoration; territorial resilience; Ebro river